Risk Factors Associated with Chronic Kidney Disease in Infants With Posterior Urethral Valve: A Single Center Study of 110 Patients Managed By Valve Ablation And Bladder Neck Incision - Amirzargar, Hossein; Shahab, Elaheh; Ghahestani, SeyyedMohammad; Hekmati, Pooya; Arshadi, Hamid (Urology Journal, 2020)
Purpose: Concurrent valve ablation and bladder neck incision is suggested as an effective and safe treatment approach in posterior urethral valve children with prominent bladder neck. We evaluated chronic kidney disease risk factors in these children. Materials and methods: We retrospectively reviewed medical records of children with posterior urethral valve and included those younger than 18 years old who underwent valve ablation and bladder neck incision at our institution. We recorded patient demographics, presenting symptoms, laboratory and radiographic data. Our primary outcome was chronic kidney disease defined as stage 3 chronic kidney disease or higher. Renal outcome risk factors such as preoperative vesicoureteral reflux and serum creatinine, age at diagnosis, adjuvant urinary diversion were analyzed. Results: A total of 110 patients met our inclusion criteria. Median age at diagnosis was 10.4 months (range 14 days to 12 years). Prenatal diagnosis in 72.7% was the most common presentation. Mean follow-up duration was 3 years and 12(10.9%) patients progressed to chronic kidney disease. Preoperative serum creatinine greater than one mg/dL was the only factor associated with progression to chronic kidney disease. Conclusion: In our group of children with posterior urethral valve ablation and bladder neck incision, initial creatinine value of greater than one mg/dL is more probably associated with renal impairment while; vesicoureteral reflux, age at diagnosis, presenting symptoms and adjuvant urinary diversion were not significant prognostic factors. Further randomized controlled evaluations are required to analyze the effects of concurrent valve ablation and bladder neck incision on renal outcome.